Planning and resource allocation models in research‐intensive universities: budget allocation and the search for excellence - Luciane Graziele Pereira Ferrero; Sergio Luiz Monteiro Salles-Filho (Humanities & Social Sciences Communications)
Abstract Research universities worldwide operate in an environment of constant change, with multiple missions, highlighting the importance of efficient and effective management of their financial resources. One of the significant concerns is the allocation of resources in budget programmes that promote institutional objectives of strategic planning related to academic excellence and socioeconomic relevance. In this context, research university managers seek to employ strategies to address this issue. The research question addressed in this article refers to whether institutional planning, linked to the allocation of resources in academic units, may contribute to promoting excellence and relevance inside academic units. This article provides an update on how research universities worldwide have approached this issue and presents a case study using data from one of the most prominent research universities in Latin America. The article examines budget allocation models and indicators with a specific emphasis on institutional strategies within the Global South. Using mathematical analysis, we propose a novel model that demonstrates the relationship between institutional strategic objectives in budget programmes and the results of each academic unit, with flexibility while preserving their particularities in terms of missions and areas of knowledge. This model allows the university and the academic units themselves to prioritise their indicators. The university can then use its budget to encourage units to move in a direction that is in the interest of the university as a whole and the units themselves.